The Relationship of Knowledge and Family Support to Self-Management in Type 2 Diabetes Mellitus Patients at the Sindangbarang Health Center Bogor - Maahirah Irchamna Hartanti; Dayan Hisni; Retno Widowati (Journal of Applied Holistic Nursing Science, 2025)
Background: Diabetes Mellitus is a long-term disease that arises when the pancreas does not produce enough insulin. According to the report International Diabetes Federation (2021) in the world, there are 537 million adults living with Diabetes Mellitus. Self-management in DM patients will not be fulfilled if there is a lack of knowledge and family support for patients. Methodology: This study was conducted using a purposive sampling technique with a Cross-Sectional approach and using a quantitative design. The sample in this study amounted to 88 Type 2 DM respondents. The data collected using questionnaires are Self-Management, Knowledge and Family Support. DKQ-24, HDFSS and DMSQ have been tested for validity and reliability with a table r value of >0.388. The research data was not distributed normally, so it was analyzed using the Spearman Rank Test Version 27. Results: A significant relationship between knowledge p-value 0.011, (r)=0.271 and family support p-value 0.001, (r)=0.350 with self-management. So that it shows the knowledge and support of families with self-management of Type 2 Diabetes Mellitus at the Sindangbarang Health Center in Bogor is included in the low category. Conclusion: There is a correlation between family knowledge and support and self-management at the Sindangbarang Bogor Health Center.